ADAPTING TRAVEL BUSINESS STRATEGIES FOR GEN Z: THE ROLE OF CROSS-BORDER PARTNERSHIPS AND TECHNOLOGY INTEGRATION - Dwiyono Rudi Susanto; Tonny Hendratono; Supina, Supina; Amin Kiswantoro; Nur Rohman (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2025)
This study explores the role of cross-border cooperation in attracting Generation Z travelers, particularly in Indonesia. With the rise of online travel agencies (OTAs) and direct service distribution by airlines and hotels, the travel industry has been reshaped by digital platforms. However, there is a gap in understanding how these collaborations meet the specific preferences of Gen Z as the potential market. The study investigates how selection factors, technology integration, and customer trust influence Gen Z’s booking intentions. A mixed-methods approach was used, combining a stratified random sampling survey and semi-structured interviews with industry professionals involved in cross-border travel partnerships. The quantitative data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that personalized experiences, trust in brands, and seamless technology integration significantly impact Gen Z's booking decisions. This research offers insights for travel companies looking to enhance engagement with this key demographic.